Evaluation of Excess Free Volume and Internal Pressure in Binary Mixtures of Methyl Methacrylate(MMA) with Alcohols - R. Vadamalar; P. Mani; R. Balakrishnan; V. Arumugam (E-Journal of Chemistry)
Methyl methacrylate (MMA) is an important monomer attracting the attention of industrialists and scientists because of its various applications and reactivity. The knowledge of thermodynamic and transport properties of MMA in alcohols and other organic solvents is useful in industrial processes. Ultrasonic and viscometric parameters offer simple, easy and accurate ways for calculating several physical parameters which throw light on molecular interactions in solutions. In this paper, the interactions of two alcohols; tert-butanol and iso-butanol with MMA are reported for the first time. Comparison has been made on the interactive nature of the two alcohols. Computation of free volume, internal pressure and excess free volume has been made for the entire concentration range. Existence of mesomeric effects of MMA is clearly seen and the role of structure of alcohols is observed.